Hubungan kemahiran berfikir secara kritis dan kreatif dengan pencapaian Matematik dalam kalangan pelajar sekolah menengah daerah Padawan, Sarawak - Tan, Sophia Soo Yee (2010)
This study aims to identify the relationship between critical and creative thinking skills (CCTS) and Mathematics performance. In addition, this study also aims to differentiate the acquisition of CCTS based on gender, Sarawak ethnicity and family income. 177 Form Two students were randomly selected from a secondary school in the Padawan District, Sarawak as the samples for this study. The instrument used in this study is a questionnaire which consist critical and creative thinking skills (CCTS) items in Form One Mathematics. Items of the CCTS test were chosen from all topics in Form One Mathematics. The data collected were analysed by using descriptive statistics (frequency, percentage, mean, standard deviation) and inferential statistics (Pearson correlation test, t-test, one-way ANOVA). The results indicated the CCTS level of students was intermediate with a mean score 52.76. Pearson correlation test analysis showed positive and high relation between CCTS and Mathematics performance (r = .873). The significance was at .01. Findings did not show any significant differences in CCTS based on gender and family income. Analysis of oneway ANOVA, however, revealed significant differences in the acquisition of CCTS by Chinese students as compared to the Malay, Iban or Bidayuh students. The other ethnic groups indicated no difference. The Chinese students scored the highest in CCTS with a mean of 60.30 compared to Malay, Iban, Bidayuh or other ethnic students. One of the implications of this study is that critical and creative thinking skills (CCTS) have to be inculcated at all levels of the teaching and learning process